American security and the global war on terror - Jacob, Edwin Daniel (Emerging technologies, ethics and international affairs, 2020)
Meditations on the abyss: America's imperial illusions -- Past prologue : understanding security in an age of terror -- A tragedy of errors : neo-conservatism, 9/11, and Iraq -- Not fade away : revolving actors and evolving tactics under Obama -- Confronting the abyss : towards a twenty-first century American security.